CONSUMER CONFIDENCE INVESTIGATION JORR TOLL SERVICE QUALITY - P, Agung Kresnamurti Rivai (The journal of contemporary issues in business and government, 2021)
The study uses descriptive and causal methods for quantitative explanation. Use this survey method for cluster sampling and use structured questionnaires for collection. In addition, LISREL version 8.8 software was used to analyze the data under structural equation modeling (SEM). These results show that customer loyalty cannot mediate the relationship between trust, satisfaction and service quality.This study aims to test the influence of trust, satisfaction, and quality of service on customer loyalty in using Toll JOOR in Indonesia. The findings show that trust, satisfaction andquality of service do not affect customer loyalty. These results imply that customer loyalty fails in mediating the relationship between trust, satisfaction and quality of JOOR Toll services in Indonesia.